Wideband Doppler Frequency Shift Measurement and Direction Discrimination Based on a DPMZM - Wei Chen; Aijun Wen; Xiaoyan Li; Yongsheng Gao; Yong Wang; Shuiying Xiang; Hongye He; Hanxiao Zheng (IEEE Photonics Journal, 2017)
A wideband microwave Doppler frequency shift (DFS) measurement approach based on a single dual-parallel Mach–Zehnder modulator (DPMZM) is proposed and experimentally demonstrated. The light wave is modulated by the transmitted and echo signals in the DPMZM to generate carrier suppressed double sidebands signals. Based on the phase difference and powers of the upper bands and lower bands of the modulated signal, the DFS value, as well as the sign, can be measured. An experiment is carried out. The DFS from –100 to +100 kHz at the carrier frequencies of 10, 20, 30, and 39 GHz is accurately measured with errors of less than $5 × {10^{ - 6}}$ Hz.